La propuesta de reforma del Derecho de obligaciones y contratos en España - Durán Rivacoba, Ramón (Revista de Derecho, 2019)
Spain has recently attempted a comprehensive review of the 226 precepts that form parts of the Spanish Civil Code, which refer to the General Part of Obligations and Contracts. This ambitious work, presented by renowned experts, is judged critically by the author, renowned Professor Spanish. In this paper evidence left in the formal defects of the “Proposal for Modernization of the Civil Code on Obligations and Contracts,” but also intractable problems left by the changes that come from the Common Law, all in the difficult by the unification of European private law and the complex inter Spanish law. The author also points out the serious defects that the proposal will generate the remaining articles of the Code, and the lack of unity and danger of creating an isolated part of the rest of the Spanish civil order without considering changes in other closely related materials with the contract. It concludes with a list of hits and new aspects count who are expected to help modernize the Spanish law properly.
Keywords: Reform; codifying; contract; obligations; patrimonialism; solidarity; cause; conservation of business; consumption; Private Law; Common Law